Validating the Radboud faces database from a child's perspective. Issue 8 (17th November 2019) - Verpaalen, Iris A. M.; Bijsterbosch, Geraly; Mobach, Lynn; Bijlstra, Gijsbert; Rinck, Mike; Klein, Anke M.
ABSTRACT: Facial expressions play a central role in diverse areas of psychology. However, facial stimuli are often only validated by adults, and there are no face databases validated by school-aged children. Validation by children is important because children still develop emotion recognition skills and may have different perceptions than adults. Therefore, in this study, we validated the adult Caucasian faces of the Radboud Faces Database (RaFD) in 8- to 12-year-old children ( N  = 652). Additionally, children rated valence, clarity, and model attractiveness. Emotion recognition rates were relatively high (72%; compared to 82% in the original validation by adults). Recognition accuracy was highest for happiness, below average for fear and disgust, and lowest for contempt. Children showed roughly the same emotion recognition pattern as adults, but were less accurate in distinguishing similar emotions. As expected, in general, 10- to 12-year-old children had a higher emotion recognition accuracy than 8- and 9-year-olds. Overall, girls slightly outperformed boys. More nuanced differences in these gender and age effects on recognition rates were visible per emotion. The current study provides researchers with recommendation on how to use the RaFD adult pictures in child studies. Researchers can select appropriate stimuli for their research using the online available validation data.